Troponin T is negatively associated with 3 tesla magnetic resonance peripheral nerve perfusion in type 2 diabetes - Jende, Johann; Mooshage, Christoph; Kender, Zoltán; Schimpfle, Lukas; Jürchott, Alexander; Nawroth, Peter Paul; Heiland, Sabine; Bendszus, Martin; Kopf, Stefan; Kurz, Felix T. (Frontiers in endocrinology, 2022)
ObjectiveThe pathogenesis of diabetic polyneuropathy (DN) is poorly understood and given the increasing prevalence of DN, there is a need for clinical or imaging biomarkers that quantify structural and functional nerve damage. While clinical studies have found evidence of an association between elevated levels of troponin T (hsTNT) and N-terminal pro brain natriuretic peptide (proBNP) with microvascular compromise in type 2 diabetes (T2D), their implication in mirroring DN nerve perfusion changes remains unclear. The objective of this study was, therefore, to investigate whether hsTNT and proBNP assays are associated with MRI nerve perfusion in T2D.MethodsIn this prospective cross-sectional single-center case-control study, 56 participants (44 with T2D, 12 healthy control subjects) consented to undergo magnetic resonance neurography (MRN) including dynamic contrast-enhanced (DCE) perfusion imaging of the right leg. Using the extended Tofts model, primary outcome parameters that were quantified are the sciatic nerve’s microvascular permeability (Ktrans), the extravascular extracellular volume fraction (ve), and the plasma volume fraction (vp), as well as hsTNT and proBNP values from serological workup. Further secondary outcomes were clinical, serological, and electrophysiological findings.ResultsIn T2D patients, hsTNT was negatively correlated with Ktrans (r=-0.38; p=0.012) and ve (r=-0.30; p=0.048) but not with vp (r=-0.16; p=0.294). HsTNT, Ktrans, and ve were correlated with peroneal nerve conduction velocities (NCVs; r=-0.44; p=0.006, r=0.42; p=0.008, r=0.39; p=0.014), and tibial NCVs (r=-0.38;p=0.022, r=0.33; p=0.048, r=0.37; p=0.025). No such correlations were found for proBNP.ConclusionsThis study is the first to find that hsTNT is correlated with a decrease of microvascular permeability and a reduced extravascular extracellular volume fraction of nerves in patients with T2D. The results indicate that hsTNT may serve as a potential marker for the assessment of nerve perfusion in future studies on DN.
Gesehen am 13.07.2022